Management of chronic obstructive pulmonary disease beyond the lungs. Issue 11 (November 2016) - Vanfleteren, Lowie E G W; Spruit, Martijn A; Wouters, Emiel F M; Franssen, Frits M E
Summary: Chronic obstructive pulmonary disease (COPD) is an umbrella term that covers many clinical subtypes with clearly different pulmonary and extra-pulmonary characteristics, but with persistent airflow limitation in common. This insight has led to the development of a more personalised approach in bronchodilator therapy, prevention of exacerbations, and advanced treatments (such as non-invasive ventilation and lung volume reduction techniques). However, systemic manifestations and comorbidities of COPD also contribute to different clinical phenotypes and warrant an individualised approach as part of integrated disease management. Alterations in bodyweight and composition, from cachexia to obesity, demand specific management. Psychological symptoms are highly prevalent, and thorough diagnosis and treatment are necessary. Moreover, prevention of exacerbations requires interventions beyond the lungs, including treatment of gastro-oesophageal reflux disease, reduction of cardiovascular risks, and management of dyspnoea and anxiety. In this Review, we discuss the management of COPD beyond the respiratory system and propose treatment strategies on the basis of the latest research and best practices.